Peningkatan Kemampuan Membaca Permulaan Menggunakan Media Happy Letters Pada Kelompok B Di TK Al Hidayah 02 Kademangan - Izza, Naswa Aqidatul; Rina Insani Setyowati; Devi Candra Nindiya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research stemmed from the low early reading skills of Group B children at Al Hidayah 02 Kindergarten, Kademangan, particularly in letter recognition, understanding sound-letter relationships, and reading simple words. The goal was to improve these skills through the interactive media "Happy Letters." The study used a two-cycle action method encompassing planning, implementation, observation, and reflection, involving 25 children aged 5–6 years. Data were obtained through observation, interviews, and documentation, then analyzed qualitatively and quantitatively. The results showed an increase in reading skills from the underdeveloped to highly developed category. Furthermore, this media also increased children's motivation, self-confidence, and participation in learning. Thus, "Happy Letters" is effective in supporting the early literacy development of preschool children.